Regional inequality and decentralization: An empirical analysis - Christian Lessmann (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper analyzes the impact of political and fiscal decentralization on regional inequalities using a unique data set which covers 56 countries at different stages of economic develop-ment. Cross-section and panel data estimations show that decentralization decreases regional inequalities in general. However, estimations using an interaction variable approach imply that the effect depends on the level of economic development. While rich countries benefit from decentralization with regard to a more equal regional income distribution, decentralization may lead to higher regional inequalities in developing and emerging economies. The results are pointing in the same direction for measures of fiscal and political decentralization implying that both - autonomy in decision making and fiscal authority - are decisive in this context. Thus, when fostering decentralization in developing countries - as proposed by international development agencies - the potential negative redistributional consequences should be taken into account.
Keywords: H11; H77; R11; 330; regional inequality; decentralization; panel data